CREB3 Plays an Important Role in HPSE-Facilitated HSV-1 Release in Human Corneal Epithelial Cells - Tejabhiram Yadavalli; Pankaj Sharma; David Wu; Divya Kapoor; Deepak Shukla (Viruses, 2022)
Herpes simplex virus type-1 (HSV-1) exploits several host factors to enhance its replication and release from infected cells. It induces the production of host enzyme heparanase (HPSE) to aid in egress. While the mechanism by which HPSE assists in viral release is well-characterized, other host factors that are recruited along with HPSE for viral release are less well understood. In this study, we identify cyclic-AMP-responsive element-binding protein3 (CREB3) as a key player in HPSE-facilitated HSV-1 egress. When CREB3 is transiently upregulated in human corneal epithelial cells, HSV-1 release from the infected cells is correspondingly enhanced. This activity is linked to HPSE expression such that HPSE-transfected corneal epithelial (HCE) cells more highly express CREB3 than wild-type cells while the cells knocked out for HPSE show very little CREB3 expression. CREB3-transfected HCE cells showed significantly higher export of HPSE upon infection than wild-type cells. Our data suggests that coat protein complex II (COPII), which mediates HPSE trafficking, is also upregulated via a CREB3-dependent pathway during HSV-1 infection. Finally, the co-transfection of CREB3 and HPSE in HCE cells shows the highest viral release compared to either treatment alone, establishing CREB3 as a key player in HPSE-facilitated HSV-1 egress.